A proposed teaching module in proof making designed for senior students in the secondary level - Luarez, Pilar C. (1975)
This study proposed a teaching module to give the reader a taste of logical proof. It aims to show the importance of proofs not only in mathematics, but also in other fields. After having learned the concepts or acquired the skills in this module, the reader will be able to construct a logical proof without assistance and will have more interest in the field of mathematics.
Thesis (M.A.T.)--University of the Philippines
Keywords: Teaching -- Aids and devices; Mathematics -- Study and teaching